2016
DOI: 10.1002/pc.24224
|View full text |Cite
|
Sign up to set email alerts
|

Layer‐by‐layer self‐assembly of aramid nanofibers on nonwoven fabric for liquid filtration

Abstract: The composite ultrafiltration membranes were fabricated by self-assembling the aramid nanofibers (ANFs) on nonwoven fabric (NF) via layer-by-layer technique. Different numbers of ANFs layers (8, 10, 12) have been selfassembled on the NF. The surface morphology, surface wettability, tensile strength, and filtration performance of as-prepared composite membranes were investigated. The results demonstrated that the surface assembled NF with the deposition of ANFs could improve their hydrophilicity and mechanical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 30 publications
(48 reference statements)
0
19
0
Order By: Relevance
“…It has been reported that the ANF can be dispersed and ionized in negatively charged polar solutions [12]. Yuan et al [13] showed that the LBL self-assembly process can be used for the preparation of composite membranes. Therefore, the negatively charged ANF can selfassemble on the surface of CNF to form composite membranes.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…It has been reported that the ANF can be dispersed and ionized in negatively charged polar solutions [12]. Yuan et al [13] showed that the LBL self-assembly process can be used for the preparation of composite membranes. Therefore, the negatively charged ANF can selfassemble on the surface of CNF to form composite membranes.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…For instance, ANF has been employed as a coating on nonwoven fabric (NF) via the LBL technique to solve the issues of large pore sizes (>10 µm), low filtration efficiency and high difficulty in filtering out nanoparticles (<100 nm) faced by conventional nonwoven filter media. [ 12 ] The obtained NF@ANF ultrafiltration membrane not only showed improved hydrophilicity and mechanical properties, but also exhibited high filtration efficiencies for 100 nm Fe 3 O 4 nanoparticles and 10 nm Au nanoparticles, approaching values of 96.4% and 91.9%, respectively, as shown in Figure A. [ 12 ] Furthermore, ANF was casted onto a nonwoven fabric to prepare a 3D interconnected hydrogel structure, as shown in Figure 19B.…”
Section: Applications Of Anfmentioning
confidence: 99%
“…[ 12 ] The obtained NF@ANF ultrafiltration membrane not only showed improved hydrophilicity and mechanical properties, but also exhibited high filtration efficiencies for 100 nm Fe 3 O 4 nanoparticles and 10 nm Au nanoparticles, approaching values of 96.4% and 91.9%, respectively, as shown in Figure A. [ 12 ] Furthermore, ANF was casted onto a nonwoven fabric to prepare a 3D interconnected hydrogel structure, as shown in Figure 19B. Taking advantage of the high solvent resistance of ANF and the porous 3D ANF hydrogel networks as well as a polyamide selective layer, the ANF‐based membrane is expected to show excellent transport performance for molecular separation in various organic solvents.…”
Section: Applications Of Anfmentioning
confidence: 99%
See 2 more Smart Citations